2016
DOI: 10.1080/02673037.2016.1208160
|View full text |Cite|
|
Sign up to set email alerts
|

Parental background and housing outcomes in young adulthood

Abstract: Scholars and policy-makers are concerned that young adults' housing opportunities are becoming more dependent on their family background. This could hinder social mobility and exacerbate inequality. Using data from three cohorts of young people drawn from the Office for National Statistics Longitudinal Study of England and Wales, this study examines how parental attributes in childhood are linked to young adults' housing outcomes two decades later. The results show that young adults' housing outcomes have chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 31 publications
7
48
1
3
Order By: Relevance
“…This restriction allows controls to be included for spatial mobility between censuses and parental attributes measured when LSMs were aged 5-14. Prior LS research shows that these are important factors in young adults' housing careers as migrants often rely on the PRS, while parental occupational advantage and homeownership increase the odds that young people enter owner-occupation (Coulter 2016). As a result of this additional restriction, the population of interest shifts subtly for the modelling work to encompass only those young adults in families in 2001 and 2011 who have also been residents in England and Wales for three consecutive censuses.…”
Section: Measures and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This restriction allows controls to be included for spatial mobility between censuses and parental attributes measured when LSMs were aged 5-14. Prior LS research shows that these are important factors in young adults' housing careers as migrants often rely on the PRS, while parental occupational advantage and homeownership increase the odds that young people enter owner-occupation (Coulter 2016). As a result of this additional restriction, the population of interest shifts subtly for the modelling work to encompass only those young adults in families in 2001 and 2011 who have also been residents in England and Wales for three consecutive censuses.…”
Section: Measures and Methodsmentioning
confidence: 99%
“…This threatens to exacerbate well-documented inequalities in young Britons' housing careers by more deeply stratifying their trajectories and experiences by class position and family background (Coulter 2016). Lennartz and colleagues (2015) show that these issues have international resonance as young people in many European countries are finding it harder to enter homeownership.…”
Section: Introductionmentioning
confidence: 99%
“…A positive influence was found for higher education (Mulder & Wagner, ) but not so in a newer study for Germany (Bayrakdar et al, ), occupational prestige (Mulder & Wagner, ), employment or occupational status (Enström Öst, ; Kurz, ; Lersch & Luijkx, ), and income (Bayrakdar et al, ; Enström Öst, ), whereas not being in employment (Coulter, ; Mulder & Wagner, ) or being unemployed (Bayrakdar et al, ; Kurz, ) were found to decrease the likelihood of moving to a self‐owned home. Moreover, living with a partner or spouse was found to increase the likelihood of becoming a homeowner (Coulter, ; Enström Öst, ). Migration background was found to be negatively related to homeownership in some countries but not in others (Coulter, ); for Germany, no influence was found (Bayrakdar et al, ).…”
Section: Theoretical Framework and State Of Researchmentioning
confidence: 94%
“…Parental homeownership was found to accelerate young adults' entry into homeownership in various contexts (Bayrakdar et al, 2018;Coulter, 2018;Kurz, 2004b;Lersch & Luijkx, 2015;Mulder, Dewilde, van Duijn, & Smits, 2015;Mulder & Wagner, 1998), whereas other parental characteristics like education (Mulder & Wagner, 1998), single parenthood or step-parenthood, and number of siblings (Bayrakdar et al, 2018;Lersch & Luijkx, 2015) were barely influential.…”
Section: Housing Careers: Empirical Findingsmentioning
confidence: 98%
See 1 more Smart Citation